Influence of the tool edge geometry on specific cutting energy at high-speed cutting - Rodrigues, Alessandro R. [UNESP] (2007)
This paper presents specific cutting energy measurements as a function of the cutting speed and tool cutting edge geometry. The experimental work was carried out on a vertical CNC machining center with 7,500 rpm spindle rotation and 7.5 kW power. Hardened steels ASTM H13 (50 HRC) were machined at conventional cutting speed and high-speed cutting (HSC). TiN coated carbides with seven different geometries of chip breaker were applied on dry tests. A special milling tool holder with only one cutting edge was developed and the machining forces needed to calculate the specific cutting energy were recorded using a piezoelectric 4-component dynamometer. Workpiece roughness and chip formation process were also evaluated. The results showed that the specific cutting energy decreased 15.5% when cutting speed was increased up to 700%. An increase of 1 °in tool chip breaker chamfer angle lead to a reduction in the specific cutting energy about 13.7% and 28.6% when machining at HSC and conventional cutting speed respectively. Furthermore the workpiece roughness values evaluated in all test conditions were very low, closer to those of typical grinding operations (∼0.20 μm). Probable adiabatic shear occurred on chip segmentation at HSC Copyright © 2007 by ABCM.